Long-term effect of repeated application of pig slurry digestate on microbial communities in arable soils - Daniela Mora-Salguero; Lionel Ranjard; Thierry Morvan; Samuel Dequiedt; Vincent Jean-Baptiste; Sophie Sadet-Bourgeteau (Heliyon)
Anaerobic digestion represents an opportunity for converting organic waste (OW) into valuable products: renewable energy (biogas) and a fertilizer (digestate). However, the long-term effects of digestates on soil biota, especially microorganisms, need to be better documented to understand the impact of digestate on soil ecosystem functioning and resilience. This study assessed the cumulative effect of repeated pig slurry digestate applications on soil microbial communities over a decade, using an in-situ approach to compare digested feedstock with undigested feedstock and other fertilization treatments. Conducted from 2012 to 2022 at an experimental field site in France, the study involved plots with identical agricultural soil management practices, differing only in fertilization treatments: mineral fertilizer, three different OW (cattle manure, pig slurry, pig slurry digestate), and a control with no organic or mineral fertilizer input. Changes in soil microbial communities were analyzed through molecular microbial biomass and diversity assessments using high-throughput sequencing targeting 16S and 18S ribosomal RNA genes. DNA extraction and molecular analyses were performed on soil samples collected at the start of the trial in 2012 and subsequently in 2017 and 2022. The long-term effects of annual digestate application over a decade include a higher soil microbial diversity in digestate-treated plots than in pig slurry-treated plots, and changes in the soil's microbial community structure and taxonomic composition resembling those observed with mineral fertilizer. Differential abundance analysis at the phylum level revealed few significant differences between digestate- and mineral fertilizer-treated plots for both prokaryotic and fungal communities. Only plots amended with cattle manure exhibited higher soil organic carbon content. Agricultural practices, along with climatic and environmental fluctuations, can significantly influence the response of soil microbial communities, thereby buffering the effects of fertilization treatments. Further research is needed to better understand the effects on soil microbial communities, considering the interactions between repeated digestate applications, different pedological contexts, and agricultural practices.